The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.socscimed.2016.12.044
|View full text |Cite
|
Sign up to set email alerts
|

Graphic health warnings as activators of social networks: A field experiment among individuals of low socioeconomic position

Abstract: Rationale Graphic health warnings (GHWs) on cigarette packages present an important tobacco control opportunity, particularly for vulnerable populations suffering a disproportionate tobacco burden. One mechanism by which GHWs may influence smoking outcomes is by prompting interpersonal discussions within health discussion networks (the set of personal contacts with whom an individual discusses health issues). Objective The study examined the association between GHW-prompted conversations within health discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 54 publications
(76 reference statements)
1
23
0
Order By: Relevance
“…Consistent with research suggesting that responses differ by the media consumer's background (Ramanadhan et al, 2017), in the present study, we found that gender, race, HPV vaccination status and eHealth literacy showed small but statistically significant effects on graphic response. Additionally, we did not assess effects of vaccine framing in the present study, but it is possible that message framing may have a greater effect on message appeal and persuasion than graphic type.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with research suggesting that responses differ by the media consumer's background (Ramanadhan et al, 2017), in the present study, we found that gender, race, HPV vaccination status and eHealth literacy showed small but statistically significant effects on graphic response. Additionally, we did not assess effects of vaccine framing in the present study, but it is possible that message framing may have a greater effect on message appeal and persuasion than graphic type.…”
Section: Discussionsupporting
confidence: 91%
“…Those that have primarily examined the frequency rather than the content of these interactions. [23][24][25][26][27] In our trial, we sought to describe the frequency, content, and nature of adult smokers' social interactions about pictorial cigarette pack warnings in the context of a randomized controlled trial that allowed for a robust comparison with text-only warnings. Characterization of social interactions about pictorial cigarette pack warnings with a large sample studied longitudinally can provide tobacco control policy makers and health communication theorists with a better understanding of how social interactions triggered by warnings may affect smoking.…”
mentioning
confidence: 99%
“…In practice, countries often put multiple pictorial warnings in circulation, to capture people’s attention and lessen wear-out. Also, warnings on the packs of other smokers in their social networks may increase the opportunities for both conversations and secondary diffusion of the messages, presenting an additional way for conversations to impact behavior (Ramanadhan et al, 2017; Southwell and Yzer, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, smoking behavior frequently happens in social settings (Moran et al, 2004; Schane et al, 2009), offering openings for conversations to take place. Several studies have found face-to-face or online social interactions were positively associated with motivation to stop smoking (Depue et al, 2015; Dunlop et al, 2008a, 2008b; Durkin and Wakefield, 2006; Hafstad et al, 1997, 1996; Ramanadhan et al, 2017; Schuster et al, 2006; Van Den Putte et al, 2011).…”
Section: Introductionmentioning
confidence: 99%